2021
DOI: 10.1007/s13555-021-00578-w
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Latest Methods of Epidermolysis Bullosa and Other Chronic Wounds Treatment Including BIOOPA Dressing

Abstract: Epidermolysis bullosa (EB) is a hereditary genetic skin disorder, classified as a type of genodermatosis, which causes severe, chronic skin blisters associated with painful and potentially life-threatening complications. Currently, there is no effective therapy or cure for EB. However, over the past decade, there have been several important advances in treatment methods, which are now approaching clinical application, including gene therapy, protein replacement therapy, cell therapy (allogeneic fibroblasts, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Choroba jest genetycznie uwarunkowaną rzadką dermatozą skórną. Powstaje w wyniku upośledzenia w połączeniu warstw skóry właściwej i naskórka [1][2][3], na skutek czego zmniejszona jest wytrzymałość skóry na obciążenia mechaniczne [4,5]. Nawet najmniejszy ucisk lub otarcie skutkuje powstaniem ubytków skóry i niegojących się pęcherzy wypełnionych surowiczym płynem, które w następstwie z powodu kruchości tkanek mogą tworzyć rozległe rany i nadżerki [6][7][8].…”
Section: Pęcherzowe Oddzielanie Się Naskórkaunclassified
“…Choroba jest genetycznie uwarunkowaną rzadką dermatozą skórną. Powstaje w wyniku upośledzenia w połączeniu warstw skóry właściwej i naskórka [1][2][3], na skutek czego zmniejszona jest wytrzymałość skóry na obciążenia mechaniczne [4,5]. Nawet najmniejszy ucisk lub otarcie skutkuje powstaniem ubytków skóry i niegojących się pęcherzy wypełnionych surowiczym płynem, które w następstwie z powodu kruchości tkanek mogą tworzyć rozległe rany i nadżerki [6][7][8].…”
Section: Pęcherzowe Oddzielanie Się Naskórkaunclassified
“…As these cell types express alternative signalling pathways to skin cells, their addition may also enable the generation of anatomic skin structures [ 78 ]. One group assessed a biological dressing composed of ~30 million Wharton’s jelly-derived mesenchymal stem cells seeded onto an acellular human skin matrix of allogeneic origin to treat an EB wound [ 79 ]. An assessment 30 days after transplantation was promising and revealed that the dressing had been infiltrated by host cells and neovascularisation had occurred [ 79 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…One group assessed a biological dressing composed of ~30 million Wharton’s jelly-derived mesenchymal stem cells seeded onto an acellular human skin matrix of allogeneic origin to treat an EB wound [ 79 ]. An assessment 30 days after transplantation was promising and revealed that the dressing had been infiltrated by host cells and neovascularisation had occurred [ 79 ]. Finally, as immune cells such as macrophages and neutrophils play an important role as inflammatory effectors during wound healing, their addition could enhance the regeneration potential of future TESSs [ 6 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%